Five new species of the genus Torodora Meyrick (Lepidoptera, Lecithoceridae, Torodorinae) from Cambodia, with a tentative check-list of the genus - Park, Kyu-Tek; Bae, Yang-Seop (Zootaxa, 2021)
Five new species of the genus Torodora Meyrick of the family Lecithoceridae are described from Cambodia. The new species are T. helvinotula Park, sp. nov., T. spathiana Park, sp. nov., T. alterniella Park, sp. nov., T. triquetrella Park, sp. nov., and T. cupriella Park, sp. nov.. In addition, Torodora macrosigna Gozmány, 1973 is reported for the first time from Cambodia, with illustration of the male genitalia for the first time.